Chemistry : an introduction to organic, inorganic and physical chemistry. - Constable, Edwin C., 1955-; Housecroft, Catherine E., 1955- (Harlow : Prentice Hall, 2010)
Chemistry provides a robust coverage of the different branches of chemistry - with unique depth in organic chemistry in an introductory text - helping students to develop a solid understanding of chemical principles, how they interconnect and how they can be applied to our lives.
Keywords: Chemie